Learning from others: an invasive lizard uses social information from both conspecifics and heterospecifics. (17th October 2018) - Damas-Moreira, Isabel; Oliveira, Daniel; Santos, Joana L.; Riley, Julia L.; Harris, D. James; Whiting, Martin J.
Abstract : Species that are able to solve novel problems through social learning from either a conspecific or a heterospecific may gain a significant advantage in new environments. We tested the ability of a highly successful invasive species, the Italian wall lizard Podarcis sicula, to solve a novel foraging task when social information was available from both a conspecific and an unfamiliar heterospecific ( Podarcis bocagei ). We found that Italian wall lizards that had access to social information made fewer errors, regardless of whether the demonstrator was a conspecific or a heterospecific, compared to Italian wall lizards that individually learnt the same task. We suggest that social learning could be a previously underappreciated, advantageous mechanism facilitating invasions.